Carrier density and thickness optimization of inxGa1-xN layer by scaps-1D simulation for high efficiency III-V solar cell - Manzoor, Habib Ullah; Tan, Aik Kwan; Ng, Sha Shiong; Zainuriah Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this study, the indium gallium nitride (InxGa1-xN) p-n junction solar cells were optimized to achieve the highest conversion efficiency. The InxGa1-xN p-n junction solar cells with the whole indium mole fraction (0 ≤ x ≤ 1) were simulated using SCAPS-1D software. Optimization of the p- and n-InxGa1-xN layer’s thickness and carrier density were also carried out. The thickness and carrier density of each layer was varied from 0.01 to 1.50 μm and 1015 to 1020 cm-3. The simulation results showed that the highest conversion efficiency of 23.11% was achieved with x = 0.6. The thickness (carrier density) of the p- and n-layers for this In0.6Ga0.4N p-n junction solar cell are 0.01 (1020) and 1.50 μm (1019 cm-3), respectively. Simulation results also showed that the conversion efficiency is more sensitive to the variations of layer’s thickness and carrier density of the top p-InxGa1-xN layer than the bottom n-InxGa1-xN layer. Besides that, the results also demonstrated that thinner p-InxGa1-xN layer with higher carrier density offers better conversion efficiency.